Hybrid peptide NTP-217 triggers ROS-mediated rapid necrosis in liver cancer cells by induction of mitochondrial leakage - Yin, Hao; Fu, Xingyan; Gao, Hanyu; Gao, Han; Ma, Yannan; Chen, Xitong; Zhang, Xueqi; Du, Shan-Shan; Qi, Yun-Kun (Frontiers in Oncology, 2023)
Liver cancer is the third leading cause of cancer-associated mortality globally, and >830,000 patients with liver cancer undergoing treatment succumbed to the disease in 2020, which indicates the urgent need to develop a more effective anti-liver cancer drug. In our previous study, nucleus-targeting hybrid peptides obtained from the fusion of LTX-315 and the rhodamine B group possessed potent anti-adherent cancer cell activity. Hybrid peptides accumulated in the cell nucleus and damaged the nuclear membrane, resulting in the transfer of reactive oxygen species (ROS) from the cytoplasm to the nucleus and the induction of apoptosis. However, the source of the high concentration of ROS within the cytoplasm is unclear. Moreover, although our previous study demonstrated that hybrid peptides possessed potent anticancer activity against adherent cancer cells, their efficacy on liver cancer remained unexplored. The current study found that the hybrid peptide NTP-217 killed liver cancer cells after 4-h treatment with a half-maximal inhibitory concentration of 14.6-45.7 μM. NTP-217 could stably accumulate in the liver tumor tissue and markedly inhibited liver tumor growth in mice. Furthermore, NTP-217 destroyed mitochondria and induced the leakage of mitochondrial contents, resulting in the generation of a substantial quantity of ROS. Unlike the apoptosis induced by 24 h of treatment by NTP-217, 4 h of treatment caused ROS-mediated necrotic cell death. These findings suggested that short-time treatment with hybrid peptides could trigger ROS-mediated rapid necrosis in liver cancer cells, and provided a basis for the future development of hybrid peptides as anti-liver cancer agents.